PENGARUH PENGETAHUAN, KETERAMPILAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Bidang Barang Milik Daerah (BMD) Provinsi Bengkulu) - Ramadhan, Destian Anugrah; Kusuma, Merta (UM. Bengkulu, 2025)
The purpose of this research is to determine the influence of knowledge, skills, and motivation on employee performance in the Regional Assets Department (BMD) of Bengkulu Province, as well as to identify which factor has the most dominant influence on employee performance. This Study uses a quantitative method with 50 respondents. The population in this study consists of employees in the Regional Assets Department (BMD) of Bengkulu Province and the sampling technique used is probability sampling. Based on the results of multiple linear regression analysis, the regression equation Y = 67.298 + 0.547 (X_1) + 0.828 (X2) + 0.850 (X3). The results of the concluded that Knowledge, Skills and Motivation have a positive and significant influence, both partially or simultaneously on Employee Performance in the Regional Assets Department (BMD) of Bengkulu Province.Keywords: Knowledge, Skills, Motivation, Performance.